Emotional Experiences on Teacher Identity Construction of EFL Novice Teachers - Fika Nurul Fadillah; Abdul Halim (Studies in Language, Education, and Culture (SeLEC), 2025)
The objective of this study is to portray novice teachers’ emotional experiences contributing to their teacher identity construction during their first years of teaching at school. This narrative study focuses on three EFL novice teachers’ narratives of the negative and positive emotional experiences they encountered as new teachers. Using a narrative framework in analyzing the data, three main themes emerge from the narrative, i.e., emotional experiences during being pre-service teachers, emotional experiences after being novice teachers, and the contrast before and after being novice teachers. This study implies that teacher educators should raise the student teachers’ awareness of their teacher identity construction before the new teachers enter the real teaching field.